Effect of Osmotic Stress on the Growth, Development and Pathogenicity of Setosphaeria turcica - Liu, Yuwei; Gong, Xiaodong; Li, Moxiao; Si, Helong; Zhou, Qihui; Liu, Xingchen; Fan, Yu; Zhang, Xiaoyu; Han, Jianmin; Gu, Shouqin; Dong, Jingao (Frontiers in Microbiology, 2021)
Osmotic stress is a severe condition frequently encountered by microorganisms; however, there is limited knowledge on the influence of hyperosmotic stress on the growth, development and pathogenicity of phytopathogenic fungi. Here, three osmotic conditions (0.4 M NaCl, 0.4 M KCl and 0.6 M sorbitol supplemented in PDA medium) were used to identify the effect of osmotic stress on the growth, development and pathogenicity of Setosphaeria turcica which is a plant pathogenic fungus and causes northern corn leaf blight disease in maize, sorghum, and related grasses. In these treatments, the growth rate of mycelium was decreased, whereas the germination rate and the yield of conidia were significantly higher under osmotic stress conditions than in the control. A pathogenicity analysis revealed that the infection hyphae formed by conidia cultured under osmotic stress were fascicular and rapidly elongated; the onset of spots caused by these infection hyphae on maize leaves was 1–2 days earlier than that cultured under normal conditions. Furthermore, the pathogenicity caused by these conidia cultured under hypertonic stress was significantly enhanced. Transmission electron microscopy indicated that the number of vesicular structures and flocculent secretion outside the cell wall were significantly increased under osmotic stress. In addition, qRT-PCR results showed that the osmotic stress condition quickly activated the HOG-MAPK pathway, up-regulated the expression of the downstream genes, and these genes were most highly expressed within 30 min of exposure to osmotic stress. By analyzing the knock-out mutants of StFPS1, an aquaglyceroporin downstream of the HOG-MAPK pathway, we found that StFPS1 was involved in the formation of appressorium and penetration peg, which affected the penetration ability of S. turcica. In summary, our work explained the correlation between osmotic stress and growth, development, and pathogenicity in S. turcica.